Influence of Sex, BMI, and Skin Color on the Accuracy of Non-Invasive Cuffless Photoplethysmography-Based Blood Pressure Measurements - Nachman, Dean; Eisenkraft, Arik; Goldstein, Nir; Ben-Ishay, Arik; Fons, Meir; Merin, Roei; Gepner, Yftach (Frontiers in Physiology, 2022)
Vital signs obtained by photoplethysmography-based devices might be influenced by subcutaneous fat and skin color. This observational comparison study aimed to test the accuracy of blood pressure (BP) measurements between a photoplethysmography-based device and cuff-based BP device in ambulatory individuals, coming for a routine BP checkup. Systolic BP (SBP) and diastolic BP (DBP) measurements were stratified based on sex, BMI (<25; 25≤BMI<30; 30≤ kg/m2), and skin color (types 1-3 and 4-6 by the Fitzpatrick scale). A total of 1548 measurements were analyzed. Correlations of SBP and DBP between the devices among males/females were between 0.914-0.987 (p<0.001), and Bland-Altman analysis showed a bias of less than 0.5 mmHg for both sexes. Correlations of SBP and DBP between the devices among BMI groups were between 0.931-0.991 (p<0.001), and Bland-Altman analysis showed a bias of less than 1 mmHg for all. Correlations of SBP and DBP between the devices among the skin color groups were between 0.936-0.983 (p<0.001), and Bland-Altman analysis showed a bias of less than 1 mmHg for all. This study shows similar and high agreements between BP measurements obtained using a PPG-based non-invasive cuffless BP device and a cuff-based BP device across sex, BMI, and skin color groups.